VIBRATION OF ELASTICALLY SUPPORTED TIMOSHENKO BEAM - Traian MAZILU (Fiabilitate şi Durabilitate, 2013)
This paper deals with the response of a Timoshenko beam elastically supported onWinkler foundation due to two harmonic forces. Such problem could be interesting to study thedynamic of the sleepers of the track. The Green’s function method has been applied to determinethe frequency-response of the beam considering both symmetrical and anti-symmetrical excitationmodes. The influence of the foundation on the vibration behavior of the beam is pointed out